The role of role-playing: quantitative insights into learning and engagement in design education - Mohd Basri, Mohd Rafaei; Rejab, Abdul Rahman; Mat Russ, Nazirah; Abdul Jalil, Nor Liza; Mohd Shariff, Mohd Rifzal; Ahmad Azam, Nur Nabila (ASIAN SCHOLARS NETWORK, 2025)
In architectural and environmental design education, motivating students and improving learning outcomes are essential for developing necessary skills and creativity. Traditional teaching methods often fail to engage students effectively. Role-playing activities, showing benefits like increased engagement and critical thinking in various contexts, can simulate real-world scenarios, enhancing learning through experimentation. The study aims to provide data-driven insights into how different role-playing activities influence student motivation and identify the most effective methods for enhancing learning outcomes in architectural and environmental design education. This study employs a quantitative post-implementation research design to evaluate the impact of role-playing on learning outcomes and student engagement within the Department of Architecture and Environmental Design. The primary objectives are to assess how role-playing activities influence students' understanding of architectural and environmental design concepts, as well as their engagement and motivation. Data is collected through a structured questionnaire administered to students after participating in various role-playing activities within their courses. The variables include the type of role-playing activity, the students' understanding of concepts and their engagement and motivation, and the overall learning experience of the students. The post-implementation questionnaire utilises 10-point linear scale items to measure students' engagement, motivation, and perceived understanding, as well as multiple-choice and short-answer questions to assess specific learning outcomes. To achieve reliable results, a sample size of 157 students from a population of 244 is utilized, providing a 95% confidence level with a 5% margin of error. Data analysis involves descriptive statistics to summarize demographic data and questionnaire responses, and inferential statistics, including correlation analysis, to explore the relationships between the types of role-playing activities and changes in engagement, motivation, and understanding. The outcomes indicate the positive impact of role-playing on students' understanding of architectural and environmental design concepts and their engagement.